Muscle Function Analysis of the Pilates Teaser in Pilates Practitioners - Jiye Yu; Changsun Kim (운동과학)
PURPOSE The purpose of this study was to investigate the muscle function involved in the Pilates Teaser. METHODS A total of 22 middle-aged women (10 in the Pilates group [PG] and 12 in the non-Pilates group [NPG]) participated in this study. During the Pilates Teaser, the hip joint angle was measured along with assessments of muscle thickness, muscle activation, and muscle fatigue. Isometric muscle strength was evaluated separately. Additionally, functional movement and dynamic balance were evaluated using the Functional Movement Screen (FMS) and the Y-Balance Test (YBT). RESULTS The women in PG maintained a significantly smaller hip joint angle than NPG (p<.01), indicating a more precise execution of the Pilates Teaser. In muscle thickness, PG showed significantly greater thickness in the rectus abdominis (p<.01), external oblique (p<.001), and rectus femoris (p<.01). Regarding muscle activation, PG exhibited significantly lower %MVC values in the rectus abdominis (p<.05) and external oblique (p<.05), and muscle fatigue in the rectus abdominis was significantly lower in PG (p<.05). In the FMS assessment, PG outperformed NPG in Deep Squat (p<.05), Hurdle Step (p<.05), Inline Lunge (p<.01), and Rotary Stability (p<.001), with significantly higher total scores (p<.001). However, no significant differences were observed between the two groups in isometric muscle strength and dynamic balance. CONCLUSIONS These findings suggest that consistent Pilates training enhances muscle thickness, muscle activation efficiency, and fatigue resistance, ultimately strengthening the powerhouse and facilitating more precise execution of the Pilates Teaser.